The Correlation of Avifauna Diversity and Its Habitat: An Observation Study at Mount Kawi Slope Waterfall, East Java: Correlation of Avifauna Diversity and Its Habitat - Lutfita Fitriana; Nia Kurniawan; Amin Setyo Leksono (Journal of Tropical Life Science, 2024)
Avifauna inhabiting mountain forest ecosystems on Java Island face severe threats from anthropogenic disturbances. Despite this, the diversity of avifauna in specific areas, such as the Hutan Lindung Pegunungan Putri Tidur (HLPPT) on the slopes of Mount Kawi, remains poorly monitored. This study focuses on assessing avifauna diversity and communities in the tourist area of Mount Kawi slope waterfalls, situated on both the southeast side in Malang Regency and the north side in Batu City. The research, conducted from January to March 2022, examined eight waterfall locations (Baung, Glotak, Luksongo, Parangtejo, Manten, Tengah, Rondo, and Sumberpitu) using the roaming method with Visual Encounter Survey (VES) and Audiovisual Encounter Survey (AES) techniques. Data analysis included considerations of conservation status, local distribution, feed specialists, diversity indices (Taxa Richness, Shannon-Wiener Diversity Index (H’), Simpson Index (D), Evenness Index (E)), and Important Value Index (IVI) as an assessment of avifaunal diversity. Researchers employed Microsoft Excel and Principal Component Analysis (PCA) to determine preferences for each character diversity index and abiotic factors in each location. Across the site, 84 species from 33 families were identified. Notably, seven species were classified as at risk (4 near-threatened, two vulnerable, and one endangered), and nine avifauna were protected. The correlation of avifauna diversity to biotic and abiotic factors was positive. These results provide essential data for further conservation management, emphasizing the protection of the forest area, tourists, waterfalls, and slopes of Mount Kawi. Additionally, studying spatial and temporal distribution is crucial for future avifauna species re-inventory efforts.